Neuroimaging of pain - Saba, Luca (Springer, 2017)
Authored by world renowned scientists, this book expertly reviews all the imaging techniques and exciting new methods for the analysis of the pain, including novel tracers, biomarker, metabolomic and gene-array profiling, together with cellular, genetic, and molecular approaches. Recent advances in human brain imaging techniques have allowed a better understand of the functional connectivity in pain pathways, as well as the functional and anatomical alterations that occur in chronic pain patients. Modern imaging techniques have permitted rapid progress in the understanding of networks in the brain related to pain processing and those related to different types of pain modulation. Neuroimaging of Pain is designed to be a valuable resource for radiologists, neuroradiologists, neurologists and neuroscientists, working in hospitals and universities from junior trainees to consultants.